Ответ:
![x_{1} = - + \frac{2\pi}{3} + 2\pi \: n \\ x_{2} = - + arccos \frac{1}{3} + 2\pi \: n x_{1} = - + \frac{2\pi}{3} + 2\pi \: n \\ x_{2} = - + arccos \frac{1}{3} + 2\pi \: n](https://tex.z-dn.net/?f=%20x_%7B1%7D%20%3D%20%20-%20%20%2B%20%20%5Cfrac%7B2%5Cpi%7D%7B3%7D%20%2B%202%5Cpi%20%5C%3A%20n%20%5C%5C%20%20x_%7B2%7D%20%3D%20%20-%20%20%2B%20arccos%20%5Cfrac%7B1%7D%7B3%7D%20%20%2B%202%5Cpi%20%5C%3A%20n)
n€Z
Пошаговое объяснение:
cos10x=cos(2×5x)=2cos^2(5x)-1 - по формуле косинус двойного аргумента
3×(2cos^2(5x)-1)+cos5x+2=0
6 cos^2(5x)+cos(5x)-1=0 - тригонометрическое квадратное уравнение, замена переменной:
cosx=t, t€[-1;1]
6t^2+t-1=0
t1=(-1/2), t2=(1/3)
обратная замена:
![t_{1} = - \frac{1}{2} \\ cosx = - \frac{1}{2} \\ x = - + arccos( - \frac{1}{2}) + 2\pi \: n \\ x = - + (\pi - arccos \frac{1}{2}) + 2\pi \: n t_{1} = - \frac{1}{2} \\ cosx = - \frac{1}{2} \\ x = - + arccos( - \frac{1}{2}) + 2\pi \: n \\ x = - + (\pi - arccos \frac{1}{2}) + 2\pi \: n](https://tex.z-dn.net/?f=%20t_%7B1%7D%20%3D%20%20-%20%20%5Cfrac%7B1%7D%7B2%7D%20%5C%5C%20cosx%20%3D%20%20-%20%20%5Cfrac%7B1%7D%7B2%7D%20%5C%5C%20x%20%3D%20%20-%20%20%2B%20arccos%28%20-%20%20%5Cfrac%7B1%7D%7B2%7D%29%20%2B%202%5Cpi%20%5C%3A%20n%20%5C%5C%20x%20%3D%20%20-%20%20%2B%20%28%5Cpi%20-%20arccos%20%5Cfrac%7B1%7D%7B2%7D%29%20%2B%202%5Cpi%20%5C%3A%20n)
![x = - + \frac{2\pi}{3} + 2\pi \: n x = - + \frac{2\pi}{3} + 2\pi \: n](https://tex.z-dn.net/?f=x%20%3D%20%20-%20%20%2B%20%20%5Cfrac%7B2%5Cpi%7D%7B3%7D%20%2B%202%5Cpi%20%5C%3A%20n%20)
![t_{2} = \frac{1}{3} \\ cosx = \frac{1}{3} \\ x = - + arccos \frac{1}{3} + 2\pi \: n t_{2} = \frac{1}{3} \\ cosx = \frac{1}{3} \\ x = - + arccos \frac{1}{3} + 2\pi \: n](https://tex.z-dn.net/?f=%20t_%7B2%7D%20%3D%20%20%5Cfrac%7B1%7D%7B3%7D%20%20%5C%5C%20cosx%20%3D%20%20%5Cfrac%7B1%7D%7B3%7D%20%5C%5C%20x%20%3D%20%20-%20%20%2B%20arccos%20%5Cfrac%7B1%7D%7B3%7D%20%20%2B%202%5Cpi%20%5C%3A%20n)